Women politicians in the UK press: not seen and not heard?. Issue 2 (3rd March 2016) - O'Neill, Deirdre; Savigny, Heather; Cann, Victoria
Abstract: This article asks questions about the ways in which female politicians are depicted in press coverage. Previous research has explored the ways in which female politicians are constructed as "other" from the male politician norm, where "men were taken to stand for the whole human population." Other work has shown that coverage emphasises their appearance or femininity. However, there has been less research on the visibility of women in politics in our media: women not only need to be involved in politics, they need to be seen to be doing political work. Through a content analysis of British press coverage using samples from the last twenty years, we examine the relative visibility of women MPs compared to men, the extent to which their voice is heard, and the context of the coverage. We argue this may well contribute to deterring women from taking part in parliamentary politics.